HBR guide to negotiating - Weiss, Jeff A. (Massachusetts Harvard Business Review Press, 2016)
Forget about the hard bargain. Whether you're discussing the terms of a high-stakes deal, forming a key partnership, asking for a raise, or planning a family event, negotiating can be stressful. One person makes a demand, the other concedes a point. In the end, you settle on a subpar solution in the middle if you come to any agreement at all. But these discussions don't need to be win-or-lose situations. Written by negotiation expert Jeff Weiss, the "HBR Guide to Negotiating" provides a disciplined approach to finding a solution that works for everyone involved. Using a seven-part framework, this book delivers tips and advice to move you from a game of concessions and compromises to one of collaboration and creativity, resulting in better outcomes and better working relationships. You'll learn how to: Prepare for your conversation - Understand everyone's interests - Craft the right message - Work with multiple parties - Disarm aggressive negotiators - Choose the best solution.